An Analysis of Anwar Zeb’s Contributions and Perspectives on the Revival of the Democratic Students Federation - Zeb, Khayam; Nawab, Habib Ullah (Annals of Human and Social Sciences, 2024)
This research paper examines the significance of the Democratic Students Federation (DSF), a left-wing student political organisation, focusing on its historical origins and revival in the 1980s. Dr. Muhammad Sarwar established the DSF in 1950, but the Pakistani government banned it in 1954. In 1981, Anwar Zeb and his associates started the revival of DSF in partnership with the Communist Party of Pakistan (CPP). The study uses an in-depth, semi-structured interview with Anwar Zeb to explore his contributions and perspectives on the resurgence of DSF. The research incorporates various methods such as historical resources, thematic analysis, archival record comparison, and ethical considerations. The study concludes that DSF emerged as a symbol of opposition to the repressive Zia dictatorship, and despite efforts to suppress it, the organisation remained resilient. Anwar Zeb later joined the Pakistan People’s Party (PPP) and is currently active in politics. The paper recommends the reinstatement of student unions as a means to address ethnic tensions, harassment, discrimination, and extremist ideologies and to cultivate competent political leaders for Pakistan’s future.